2019
DOI: 10.1177/0958305x19843104
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and economic effects of sulfur dioxide emissions trading pilot scheme in China: A quasi-experiment

Abstract: In this study, we consider the sulfur dioxide emissions trading pilot scheme (SETPS) of China, with pilot provinces as the treatment group and other provinces as the control group. We employ the difference-in-differences method to estimate the effects of the SETPS on pollution mitigation and economic growth. Results show that the SETPS plays a robust role both in China’s industrial sulfur dioxide abatement and in economic growth. Furthermore, by applying regression analysis to explore regional heterogeneity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…Previous studies have examined the impacts of ETS policy implementation on emissions reductions, economic performance, technological innovation, and productivity. In terms of emissions reductions, Hou et al [ 9 ] showed that the 2007 SO 2 ETS pilot policy in China significantly reduced SO 2 emissions and SO 2 intensity, consistent with Wu et al [ 29 ] findings. Zhang et al [ 30 ] pointed out that although the carbon ETS in China is still accompanied by an immature market environment, inadequate infrastructure, limited emissions trading, and low market liquidity, it has had a significant effect on China’s carbon emissions reductions in recent years.…”
Section: Literaturesupporting
confidence: 63%
“…Previous studies have examined the impacts of ETS policy implementation on emissions reductions, economic performance, technological innovation, and productivity. In terms of emissions reductions, Hou et al [ 9 ] showed that the 2007 SO 2 ETS pilot policy in China significantly reduced SO 2 emissions and SO 2 intensity, consistent with Wu et al [ 29 ] findings. Zhang et al [ 30 ] pointed out that although the carbon ETS in China is still accompanied by an immature market environment, inadequate infrastructure, limited emissions trading, and low market liquidity, it has had a significant effect on China’s carbon emissions reductions in recent years.…”
Section: Literaturesupporting
confidence: 63%
“…In neoclassical theory, the company is presumed to be well informed and rational and seeks profit maximization. Spending more on environmental mitigation would result in higher investment (Wu et al, 2019). This mitigation activity will add extra costs and deduct the performance of a company.…”
Section: Ep and Fpmentioning
confidence: 99%
“…In order to test the impact of the environmental target responsibility system on firm's pollutant emissions, this paper constructs a DID model as follows (Long et al, 2018;Zhang et al, 2018;Wu et al, 2019;Chen et al, 2021):…”
Section: Did Model Of Pollutant Emissionsmentioning
confidence: 99%
“…Since the formulation of environmental protection targets is from top to bottom, and the upper-level government assesses and supervises the implementation of environmental goals of local government officials, the environmental target responsibility system is a typical mandatory environmental regulation. Its pollutant emission reduction effect has been demonstrated by many scholars (Calel and Dechezleprêtre, 2016;Wu et al, 2019;Zheng et al, 2021). However, some scholars still question whether the effects of mandatory environmental regulations are sustainable.…”
Section: Introductionmentioning
confidence: 99%